2019
DOI: 10.17557/tjfc.509134
|View full text |Cite
|
Sign up to set email alerts
|

Line x Tester Analysis for Yield and Fiber Quality in Cotton (Gossypium hirsutum L.)

Abstract: This experiment was conducted in order to estimate gene action, combining ability and heterotic effects for yield and quality characters by the line x tester analysis, involving 5 lines and 4 testers with 20 crosses in cotton (Gossypium hirsutum L.). The ratio of general and specific ability variance revealed non-additive gene action effects for seed cotton yield, fiber length, fiber strength and ginning percentage and additive gene action for fiber fineness and reflectance degree. Claudia, Gloria and Bali 308… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…BGKM-3, one of the lines, is showed very significant and positive GCA in terms of cotton yield, fiber yield, earliness and fiber length except for ginning outturn, while positive GCA showed in fiber fineness, fiber strength and fiber uniformity. Stoneville 468, one of the testers, was showing as smilarity with Unay et al (2019) for cotton yield, fiber yield and earliness, Claudia is showed smilarity again in term of ginning outturn, fiber length, fiber fineness, fiber strength and fiber uniformity again with Unay et al (2019). On the other hand, BGKM-3 x Stoneville 468 F1 hybrid combined seed cotton yield with fiber quality, and was showed positive heterosis in seed cotton yield, fiber yield, earliness, fiber length and fiber uniformity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BGKM-3, one of the lines, is showed very significant and positive GCA in terms of cotton yield, fiber yield, earliness and fiber length except for ginning outturn, while positive GCA showed in fiber fineness, fiber strength and fiber uniformity. Stoneville 468, one of the testers, was showing as smilarity with Unay et al (2019) for cotton yield, fiber yield and earliness, Claudia is showed smilarity again in term of ginning outturn, fiber length, fiber fineness, fiber strength and fiber uniformity again with Unay et al (2019). On the other hand, BGKM-3 x Stoneville 468 F1 hybrid combined seed cotton yield with fiber quality, and was showed positive heterosis in seed cotton yield, fiber yield, earliness, fiber length and fiber uniformity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that different gene effects in the traits examined. Unay et al (2019) reported the dominant gene effects on seed cotton yield, ginning outturn fiber length and strength, in contrast, Prakash et al (2018) and Roy et al (2018) reported that the additive gene effects are more important.…”
Section: Line X Tester Analysis and Ratio Of Gca/scamentioning
confidence: 98%
“…Boyaci (2011) reported that fiber fineness, boll seed weight and earliness characteristics showed negative heterosis, while both positive and negative heterosis could be seen in other characteristics. In addition, many researchers determined that non-additive genes, in other words, dominant, epistatic or dominant × epistatic genes were effective in the management of yield, ginning percentage, earliness, single boll seed weight, 100 seed weight, fiber fineness and fiber strength traits in Line × Tester populations (Ashokkumar et al, 2010;Saravanan et al, 2010;Kalpande et al, 2014;Sawarkar et al, 2015;Sajjad et al, 2016;Guvercin, 2016;Patil et al, 2018;Ullah et al, 2020;Unay et al, 2020). Basal et al (2009) and Karademir et al (2009) reported that fiber length is managed by additive genes.…”
Section: Introductionmentioning
confidence: 99%
“…In line-tester analysis, the additive variance was significant for fiber length, fiber fineness and fiber elongation, and non-additive gene effects for seed cotton yield, lint yield, lint%, fiber strength and fiber uniformity (Karademir et al, 2009;Shaukat et al, 2013;Memon, 2017;Mahrous, 2018;Makhdoom et al, 2019). Likewise, the ratio δ 2 GCA/δ 2 SCA depicted the predominance of non-additive types of gene action for plant height, seed cotton yield and its components and fiber length and fiber strength (Karademir et al, 2009;Khokhar et al, 2018;Munir et al, 2018;Patil et al, 2018;Unay et al, 2019). The variances due to SCA were more than GCA variances for various fiber quality parameters which indicates the preponderance of non-additive nature of gene action (Ali & Awan, 2009;Shaukat et al, 2013;Simon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%